Political risk and quality of governance as determinants of foreign direct investments in the transition countries - Miloš Dašić (Economic Themes, 2022)
This paper uses dynamic panel data methods to examine the political indicators and governance quality indicators as determinants of foreign direct investment (FDI) into the Balkan and non-Balkan countries in transition. Our empirical model shows that the determinants, such as political terror scale and the control of corruption, have significant and plausible effects in the Balkan and non-Balkan countries in transition. In addition, analyzed factors such as government effectiveness and regulatory quality, which play important political roles in determining foreign direct investment flows into countries in transitions and help explain the differing attractiveness of individual countries to foreign investors in our empirical model, do not play a significant role in the inflow of foreign direct investment.
Keywords: P27; E20; E27; F21; 330; inflow FDI; governance quality; Balkan and non-Balkan countries